2018
DOI: 10.1093/icb/icy056
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Basis for Adaptive Variation in Aerobic Performance in High-Altitude Deer Mice

Abstract: Mitochondria play a central role in aerobic performance. Studies aimed at elucidating how evolved variation in mitochondrial physiology contributes to adaptive variation in aerobic performance can therefore provide a unique and powerful lens to understanding the evolution of complex physiological traits. Here, we review our ongoing work on the importance of changes in mitochondrial quantity and quality to adaptive variation in aerobic performance in high-altitude deer mice. Whole-organism aerobic capacity in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 84 publications
2
36
0
Order By: Relevance
“…Modeling of the O2 transport pathway revealed that increases in Hb-O2 affinity would only be expected to enhance V O2max in hypoxia if O2 diffusing capacity were increased to augment tissue O2 extraction. Importantly, recent evidence suggests that high-altitude mice do possess an enhanced capacity for O2 diffusion through the evolution of a highly aerobic skeletal muscle phenotype (36)(37)(38)(39)(40). This involves greater capillary density, higher proportional abundance of oxidative fibre types, increased volume density of subsarcolemmal mitochondria, and augmented mitochondrial respiratory capacities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling of the O2 transport pathway revealed that increases in Hb-O2 affinity would only be expected to enhance V O2max in hypoxia if O2 diffusing capacity were increased to augment tissue O2 extraction. Importantly, recent evidence suggests that high-altitude mice do possess an enhanced capacity for O2 diffusion through the evolution of a highly aerobic skeletal muscle phenotype (36)(37)(38)(39)(40). This involves greater capillary density, higher proportional abundance of oxidative fibre types, increased volume density of subsarcolemmal mitochondria, and augmented mitochondrial respiratory capacities.…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with a higher V O2max in chronic hypoxia, high-altitude deer mice also exhibit higher pulmonary O2 extraction, arterial O2 saturation, cardiac output, and tissue O2 extraction than their lowland counterparts (9,35). The latter is associated with several evolved changes in skeletal muscle phenotype and mitochondrial function (36)(37)(38)(39)(40). Highlanders have also evolved a higher Hb-O2 affinity as a result of amino acid replacements in duplicated genes that encode the α-and β-chain subunits of the α2β2 Hb tetramer (5,6,15,20,21,23,24,26,34,41).…”
Section: Main Text Introductionmentioning
confidence: 99%
“…However, except for studies of a few key proteins like hemoglobin ( Natarajan et al, 2018 ; Natarajan et al, 2015 ; Projecto-Garcia et al, 2013 ; Storz et al, 2010 ), we still know little about whether convergent phenotypic changes have arisen across independent high-altitude lineages, particularly for the pathways of energy metabolism that support locomotion and thermogenesis. Metabolic genes have been outliers in genome scans of selection in high-altitude taxa ( Qu et al, 2015 ), and recent studies in high-altitude populations of mice and humans point towards skeletal muscle as a common target of selection ( Lundby and Calbet, 2016 ; Scott et al, 2018 ). However, the extent to which convergent reorganization of metabolic pathways has occurred across high-altitude taxa to help sustain locomotion and thermogenesis in hypoxia remains unclear, particularly across species that independently colonized high altitude in the same geographic region.…”
Section: Introductionmentioning
confidence: 99%
“…Given the functional importance of OXPHOS, variations in these genes can directly influence metabolic performance (Escalona, Weadick, & Antunes, 2017;da Fonseca, Johnson, O'Brien, Ramos, & Antunes, 2008;Hood et al, 2018;Li et al, 2017;Scott, Guo, & Dawson, 2018). Four complexes (I, III, IV, and V) have subunits encoded by genes in both the nuclear and mitochondrial genomes, whereas one (II) is encoded exclusively in the nuclear genome.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that non-neutral mutations in mitochondrial-encoded protein-coding genes (PCGs) are associated with adaptations of animals to different environments (Almeida, Maldonado, Vasconcelos, & Antunes, 2015;da Fonseca et al, 2008;Luo, Yang, & Gao, 2013;Pfenninger et al, 2014;Scott et al, 2018Scott et al, , 2011Yuan et al, 2018;Zhang, Yang, & Zhang, 2019).…”
Section: Introductionmentioning
confidence: 99%